Crushing Behavior of Hexagonal Composite Tubes - Al Kabir, Munir Faraj M. (2004)
An experimental and finite element analysis was carried out to investigate effect of hexagonal composite tube dimension on failure mode and energy absorption capability. Throughout this investigation, the hexagonal tube with different aspect ratio of length to thickness (Llt) varying from 30 to 100 and different hexagonal angles varying from 35" to 60" in 5" increments were investigated under the axial load condition. All the hexagonal tubes tested were fabricated from fabric plain weave /epoxy. The effect of hexagonal geometry on the load carrying capacity and energy absorption capability was presented. A finite element model to predict the load carrying capacity, deformation mesh, stress contours at pre-crush stage of hexagonal tube under an axial load condition were developed.Experimental results show that the hexagonal geometry (length to side diminutions) increases the load carrying capacity by 32.0, 13.8, 2.land 18.7% respectively for hexagonal side angle of 35", 45", 50°, and 55" respectively, the load carrying capacity is reduce by 49.6 and 29.6% for hexagonal side angles of 4O0and 6O0repectively. The energy absorption also increases by 1.42 and 1.5 % for hexagonal side angles of 35" and 6O0respectivelyand energy absorption is reduced by 48.6, 11.6, 20.0and 46,7% respectively for hexagonal side angle of 40°, 45", 50" and 55" respectively. Finite element model predictions are correlated with experimental results. The variation between the experimental and finite element is in the range of 5.9% to 9.8% .The effect of geometry of fabric plain weavelepoxy (Ring Chain System With Hexagonal Shape) on crushing behavior, energy absorption capability, crush failure loads and failure modes were also investigated. Failure modes were examined using several photographs taken during the crushing stages for each experiment. The main failures modes that occured during the experiment are local buckling, catastrophic and matrix failure modes.